Habituation Strategies for Developing Religious and Moral Values in Schools - Khoirun Nissa Febriyanti Sholikah; Ratih Kumala Wijayanti; Miftahudin Miftahudin; Darsinah Darsinah; Murfiah Dewi Wulandari (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The cultivation of moral and religious values is a critical component of early education, particularly in faith-based institutions. Specific Background: Muhammadiyah Elementary School 13 Makam Bergola emphasizes religious habituation as part of its character education agenda. Knowledge Gap: However, limited studies have examined how structured school programs integrate with home environments to sustain value-based education. Aims: This study aims to explore the implementation and effectiveness of moral and religious value habituation at the school through a descriptive qualitative approach involving interviews with teachers, students, and parents. Results: Findings reveal that six core indicators—religious habituation, worship practices, praying, polite behavior, positive conduct, and greeting etiquette—are effectively embedded in daily school routines through strategies such as routine programming, teacher modeling, and reward systems. Novelty: The study highlights the innovative integration of parenting education and home-school collaboration to address the inconsistency of value practice between school and home environments.Implications: These results underscore the necessity of a holistic, school-family partnership model for sustainable moral and religious development in elementary education. Highlights: Emphasizes consistent religious and moral value habituation at school. Highlights collaboration between teachers and parents to reinforce values. Introduces parenting education as a solution to home-school inconsistency. Keywords: Character Education, Religious Values, Moral Values, Habits, Elementary School